Geographical aspects of the changes of Hungary’s deconcentrated state administration system between 1990 and 2012 - Kozma Gábor; Barta Attila (Bulletin of Geography. Socio-Economic Series, 2013)
One of the most important segments of the post-1990 transformation of territory-based administration in Hungary was the changing of the geographical structure of deconcentrated state administrative organisations. The study, on the one hand, provides a brief overview of the history of deconcentrated state administrative organisations in Hungary, and discusses the regional characteristics of the organisational transformations after the political changes, taking six moments in time (the middle of 1994, 1998, 2002, 2006, 2010 and 2012 respectively) as the basis. On the other hand, using the same six snapshots in time, it examines which settlements experienced favourable or unfavourable changes, and what factors influenced the selection of the seats for these institutions.